2012
DOI: 10.1093/icesjms/fss084
|View full text |Cite
|
Sign up to set email alerts
|

Climate-related variations in the occurrence and distribution of mackerel (Scomber scombrus) in Icelandic waters

Abstract: Astthorsson, O. S., Valdimarsson, H., Gudmundsdottir, A., and Óskarsson, G. J. 2012. Climate-related variations in the occurrence and distribution of mackerel (Scomber scombrus) in Icelandic waters. – ICES Journal of Marine Science, 69: . Based on long-term investigations on sea temperature in Icelandic waters, five climatic periods are defined from the mid-1880s until today. These are a cold period between 1880 and 1920, a warm period between 1921 and 1964, a cold period between 1965 and 1971, one of intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 13 publications
2
93
0
Order By: Relevance
“…Herring and mackerel are very common food items of the gannet in the core of its distribution and recently also in northern Norway (Nelson 2002;Barrett 2016) such that their northward expansion made way for the opportunistic spread of the gannet to Bjørnøya. This mirrors the recolonization by gannets of Funk Island, off Newfoundland, in the 1930s and the establishment of new gannet colonies in eastern Iceland in the 1940s when mackerel appeared off the coasts during periods of warm water (Gudmundsson 1953;Montevecchi & Myers 1997;Astthorsson et al 2012;Freydis Vigfúsdottir, pers. comm.).…”
Section: Discussionmentioning
confidence: 81%
“…Herring and mackerel are very common food items of the gannet in the core of its distribution and recently also in northern Norway (Nelson 2002;Barrett 2016) such that their northward expansion made way for the opportunistic spread of the gannet to Bjørnøya. This mirrors the recolonization by gannets of Funk Island, off Newfoundland, in the 1930s and the establishment of new gannet colonies in eastern Iceland in the 1940s when mackerel appeared off the coasts during periods of warm water (Gudmundsson 1953;Montevecchi & Myers 1997;Astthorsson et al 2012;Freydis Vigfúsdottir, pers. comm.).…”
Section: Discussionmentioning
confidence: 81%
“…Subsequently the temperatures have remained high and even declined somewhat since 2010 (Larsen et al, 2012). Further, the near-surface summer temperatures south of Iceland, in the Iceland Basin and Irminger Sea, have been within the range that the mackerel occupies, and in the range that the mackerel prefers, for several decades (Astthorsson et al, 2012;MacKenzie et al, 2014). Hence we find it unlikely that temperature in itself has induced the recent mackerel expansion.…”
Section: Figurementioning
confidence: 99%
“…Thus it appears that average summer temperatures ( July-August) in the Norwegian Sea have not changed enough to explain the post-2006 expansion of the feeding area. On the contrary, recent studies have shown that the expansion areas in the Irminger Sea, Icelandic waters and the northern Norwegian Sea have, for decades, had summer temperatures not only tolerable (> 5 °C), but well in the temperature range that mackerel occupy (Astthorsson et al, 2012;Utne et al, 2012;MacKenzie et al, 2014). During spawning, mackerel seem to be feeding more sporadically, while towards the end of spawning mackerel become meagre and start to feed (Lockwood et al, 1981;ICES, 2014c).…”
Section: Introductionmentioning
confidence: 99%
“…Commercial landings suggested prevalence of mackerel in Icelandic waters (Astthorsson et al, 2012;ICES, 2013a). While mature mackerel had traditionally been found here numbers were generally small.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, also 0-and 1-groups mackerel have been observed in the area (Astthorsson et al, 2012). The increase in mackerel around Iceland during the summer feeding season meant that mackerel distribution has extended beyond the area regulated in the original management plan (ICES, 2013a).…”
Section: Introductionmentioning
confidence: 99%